DINAMIKA PENANAMAN NILAI-NILAI MORAL PANCASILA DALAM MENUMBUHKAN SIKAP BELA NEGARA DI TINGKAT SEKOLAH DASAR - Putri, Ananda; Azis , Elinda; Zaharani , Nadya; Aretha , Elvina; Subakdi, Subakdi; Kayowuan , Kayus; Suprima, Suprima (Civilia: Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2024)
Pancasila as the ideology of the Indonesian nation as well as being used as the basis of the Indonesian state has noble values that are important to instill from an early age. In addition, Pancasila is also the way of life of the Indonesian people. The influence of the globalization era on the values of Pancasila is very impactful with the weakening of the power of education control by the state and the decline in the moral quality of elementary school students. Technological advances due to the rapid flow of globalization, greatly changing the pattern of teaching in the world of education. Because the influence of the globalization era that is so fast can fade the ideological values of Pancasila and the attitude of state defense in the lives of generation Z and Alpha. This article will describe the dynamics of the moral values of Pancasila that must be implemented so that the values of Pancasila in fostering the attitude of state defense remain strong, it is necessary to strengthen the values of Pancasila to the next generation of the nation, especially to students from the elementary school level first. This article is made to continue to make Pancasila as a guideline in everyday life to foster an attitude of state defense from an early age, so as to make the next generation of nationalists, responsible, democratic, and become the next generation who uphold the values of Pancasila. This article is made using the community service method (PKM) by paying attention to activity planning, implementation, and evaluation stages.